Problemfelder der Kriminalwissenschaft: interdisziplinäre Einsichten - Bachhiesl, Christian Wilhelm; Bachhiesl, Sonja Maria; Köchel, Stefan; Gross, Hanns (Austria: Forschung und Wissenschaft, 2017)
Literaturangaben